PELANGGARAN HUKUM TERHADAP KARYA CIPTA BUKU HASIL TERJEMAHAN DALAM BENTUK ELEKTRONIK : PERSPEKTIF UU HAK CIPTA - Rama, Bagus Gede Ari; Mahadewi, Kadek Julia (Kerta Dyatmika, 2023)
The rapid advancement of digital technology has significantly influenced public behavior, particularly the shift in reading interests toward digital formats such as e-books. However, this ease of access also raises potential legal issues, especially concerning copyright infringement of translated works in electronic form. This study aims to analyze the legal consequences of copyright infringement related to translated e-books and to identify preventive measures necessary to avoid such violations. The research employs a normative legal method with a statutory approach. The findings indicate that copyright infringements may be resolved through Alternative Dispute Resolution (ADR), commercial courts, and are subject to criminal sanctions pursuant to Article 113 paragraphs (1) to (4) of the Copyright Law. Furthermore, the translation of a copyrighted work into an electronic format does not constitute a copyright violation if the translator has obtained a license from the copyright holder and has registered the license agreement in writing with the Ministry of Law and Human Rights. Thus, understanding copyright law provisions is essential in addressing the legal challenges posed by the digital era.